Impact of state funding on rail system and agricultural cooperatives in Wisconsin - Schoenborn, Sara (Kansas State University, 2018)
Since the introduction of railroad systems to the United States in the early- to mid- 1800s, agricultural producers – particularly those in the grain, fertilizer and fuel industries – have benefitted from increased access to national and global markets. This study is designed to examine the Wisconsin 2017-2019 Biennium Budget as an indication of the state’s political desire to fund the state’s rail system and address the implications related to cooperative performance and competitive advantage in the agricultural markets. The objective is to collect data from Wisconsin cooperatives and: 1) determine cooperatives’ current use of rail; 2) estimate the average rail transportation cost for cooperatives; and 3) discuss whether cooperatives should evaluate (if not consider) switching from rail to another mode of transportation. When reviewing the participants’ current use of rail, the research findings suggest that a number of organizations use this method of transportation for both inbound and outbound business. In addition, the majority surveyed indicated competitors and/or customers also use rail as a mode of transportation. The research findings suggest that agricultural cooperatives in Wisconsin should independently evaluate the costs and/or benefits of switching from rail to another mode of transportation and the impact a change of this nature would have on the cooperatives’ input suppliers as well as end customers. The implications might impact future profitability or financial viability of the cooperative.
Keywords: Transportation; Rail; Cooperatives; Wisconsin; State budget